Review of Newly Identified Functions Associated With the Heat-Labile Toxin of Enterotoxigenic Escherichia coli - Duan, Qiangde; Xia, Pengpeng; Nandre, Rahul; Zhang, Weiping; Zhu, Guoqiang (Frontiers in Cellular and Infection Microbiology, 2019)
Heat-labile toxin (LT) is a well-characterized powerful enterotoxin produced by enterotoxigenic Escherichia coli (ETEC). This toxin is known to contribute to diarrhea in young children in developing countries, international travelers, as well as many different species of young animals. Interestingly, it has also been revealed that LT is involved in other activities in addition to its role in enterotoxicity. Recent studies have indicated that LT toxin enhances enteric pathogen adherence and subsequent intestinal colonization. LT has also been shown to act as a powerful adjuvant capable of upregulating vaccine antigenicity; it also serves as a protein or antigenic peptide display platform for new vaccine development, and can be used as a naturally derived cell targeting and protein delivery tool. This review summarizes the epidemiology, secretion, delivery and mechanisms of action of LT, while also highlighting new functions revealed by recent studies.